Safety and Efficacy of Autologous Dermal Fibroblast Injection to Enhance Healing After Full-Thickness Rotator Cuff Repair: First-in-Human Pilot Study. Issue 11 (9th November 2021) - Yoon, Ji Young; Park, Joo Hyun; Rhee, Sung-Min; Jeong, Hyeon Jang; Han, Jikhyon; Lee, Ji-Hye; Jeon, Saewha; Oh, Joo Han
Background: There is growing interest in various biological supplements to improve tendon healing in patients after arthroscopic rotator cuff repair. The ideal biological supplement to strengthen rotator cuff remains unknown. Purpose: To assess the safety and efficacy of autologous cultured dermal fibroblast (ADF) injection on tendon-to-bone healing in patients after arthroscopic rotator cuff repair. Study Design: Case series; Level of evidence, 4. Methods: Included were 6 patients who underwent arthroscopic rotator cuff repair between June 2018 and March 2020; all patients had a full-thickness rotator cuff tear (>2 cm) involving the supraspinatus and infraspinatus tendons. The patients were injected with ADF between the repaired tendon and footprint during arthroscopic rotator cuff repair using the suture bridge technique. The safety of ADFs and the procedure was evaluated at 5 weeks postoperatively, and the anatomical healing of the repaired tendon was accessed at 6 months postoperatively using magnetic resonance imaging and at 12 months using ultrasonography. Outcomes including shoulder range of motion (ROM), visual analog scale (VAS) for pain, and functional scores were measured at 6 and 12 months postoperatively. Results: Adverse reactions to ADF injection were not observed at 6 months after surgery. VAS and functional scores at 6 and 12 months postoperatively were significantly improved compared with preoperative scores (all P < .05). However, there was no significant difference on any ROM variable between preoperative and postoperative measurements at 6 and 12 months (all P > .05). No healing failure was found at 6 and 12 months postoperatively. Conclusion: There was no adverse reaction to ADF injection, and all patients had successful healing after rotator cuff repair. A simple and easily accessible ADF injection may be a novel treatment option for increasing the healing capacity of torn rotator cuff tendons. Further clinical research is needed to verify the study results.